The Role of External Assurance in Moderating the Effect of Sustainability Reporting Quality on Firm Value - Anisa, Yolita Deantri; Nikmah (Yayasan Ilomata, 2024)
This quantitative research aims to examine the role of external assurance in moderating the effect of sustainability reporting quality on firm value in all companies listed on the Indonesia Stock Exchange in 2018-2022. This study uses purposive sampling to determine the research sample so that 27 companies that meet the criteria are obtained. Data analysis was carried out with the Moderated Regression Analysis (MRA) model using IBM SPSS. The results found that the sustainability reporting quality indicated by the disclosure of sustainability reporting has a positive effect on firm value because the more items disclosed, the higher the sustainability reporting quality which has an impact on increasing firm value. Then this study found that external assurance does not moderate the effect of sustainability reporting quality and firm value because there are still several influencing factors. The results of this study contribute empirically that companies still have to improve the sustainability reporting quality through more voluntary disclosures to increase firm value, even though the existence of external assurance in sustainability reporting has not been considered by investors.